PEMBERDAYAAN MASYARAKAT NAGARI PERSIAPAN SIDODADI, KABUPATEN PASAMAN BARAT MELALUI TEKNOLOGI DETEKSI KEBUNTINGAN DINI DAN INOVASI PERMEN SAPI UNTUK PENGEMBANGAN SAPI POTONG - Ferry Lismanto Syaiful; Efrizal Efrizal; Fauzia Agustin; Uyung Gatot S. Dinata (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
Kanagarian Preparation Sidodadi is one of the villages in Kinali District, West Pasaman Regency. The majority of the people are eyed as farmers and ranchers. The main commodities produced by farmers are corn, rice and mustard coconut, while the main livestock commodities are cattle. In addition, this nagari has a fairly large area of agricultural land that has great potential to be a place for developing beef cattle. The purpose of this activity is 1. to transfer early pregnancy detection technology and 2. the use of cow candy as a feed supplement for livestock to increase livestock production. While the approach used in the implementation of the KKN-PPM program in the Sidodadi nagari community is a participatory Rural Appraisal (PRA) approach that involves all elements of the community starting from the sub-district, wali nagari, head of jorong, head of hamlet, ninik mamak, housewives and youth. The stages of this activity include the preparation, implementation and evaluation stages. There were 24 students involved, consisting of various faculties at Andalas University. The results of the activities obtained are: 1. Breeders have begun to be motivated to add knowledge in the cultivation of good and profitable beef cattle, 2. Service activities in the form of counseling to maintain beef cattle through the application of technology given to farmers are very attractive to farmers to do cattle business cut apart from rice paddy business to increase family income, 3. Farmers and the community can master the technology of early pregnancy detection of beef cattle, 4. Farmers can make cow candy is very possible to be done at the household scale or can also be a factory to increase income. From the results of the activities it can be concluded that the activities that have been carried out are categorized as successful. This can be seen at the time when the activities of the breeders/farmer groups and the community are very large towards the development of beef cattle business.